New record of Holotrichia serrata (Fabricius) (Coleoptera, Scarabaeidae, Melolonthinae) infestation on cassava - Nafeesa, M.; Sreedevi, K.; Murugan, M. (ENTOMON, 2026)
Holotrichia serrata (Fabricius) (Coleoptera, Scarabaeidae, Melolonthinae), a polyphagous pest was noted for the first time infesting cassava in Kerala. Extensive feeding on the foliage was observed. The number of beetles per plant ranged from 25 to 85 during the infestation and defoliation ranged from 45 to 70 per cent. Stunted growth and yellowing of the plants were observed. After four months, the grub population was observed in the root zone, which ranged from 4-12 numbers per plant. The occurrence of another species, Anomala dussumieri Blanchard (Coleoptera, Scarabaeidae, Rutelinae), was also noticed along with H. serrata in the infested field. But A. dussumieri strictly avoided cassava leaves for feeding and copulation in the field and in the lab.